2011
DOI: 10.1021/bi102042t
|View full text |Cite
|
Sign up to set email alerts
|

The Second Coordination Sphere of FIH Controls Hydroxylation

Abstract: The factor inhibiting HIF (FIH) is a proximate oxygen sensor for human cells, hydroxylating Asn803 within the α subunit of the hypoxia inducible factor (HIF). FIH is an α-ketoglutatrate (αKG) dependent, non-heme Fe(II) dioxygenase, in which Fe(II) is coordinated by a (His2Asp) facial triad, αKG, and H2O. Hydrogen bonding between the facial triad, the HIF-Asn803 sidechain, and various second-sphere residues suggests a functional role for the second coordination sphere in tuning the chemistry of the Fe(II) cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(67 citation statements)
references
References 40 publications
8
59
0
Order By: Relevance
“…In close agreement with previously reported values,(14, 31) the K M(αKG) remained constant at 20 ± 2μM for all CTAD concentrations. The regression plot of k cat /K M(αKG) as a function of [CTAD] passed through the origin, as expected for ordered sequential binding of αKG prior to CTAD (Figure 3).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In close agreement with previously reported values,(14, 31) the K M(αKG) remained constant at 20 ± 2μM for all CTAD concentrations. The regression plot of k cat /K M(αKG) as a function of [CTAD] passed through the origin, as expected for ordered sequential binding of αKG prior to CTAD (Figure 3).…”
Section: Resultssupporting
confidence: 93%
“…Previously we showed tight coupling between succinate production and CTAD hydroxylation in H 2 O. (14) Here we observed that FIH’s two half reactions remained tightly coupled in D 2 O, with C equal to unity within experimental uncertainty( C = 1.1 ± 0.1) (Table 2). …”
Section: Resultssupporting
confidence: 67%
“…The sites are primed for reactivity with O 2 by the binding of a-KG, which serves as a bidentate ligand to Fe. A recent study [16] examined the role of OSC in the reactivity of one member of this family, "factor inhibiting HIF-1" (FIH). FIH participates in human O 2 sensing by catalyzing hydroxylation of C b of Asn803 in the C-terminal transactivation domain (CTAD) of hypoxia-inducible factor (HIF) [17].…”
Section: A-ketoglutarate-dependent Fe Dioxygenasesmentioning
confidence: 99%
“…In light of the fact that primary substrate does not bind directly to Fe 2+ , and the observation that contacts throughout the active site greatly impact reactivity, 15,55 it appears that substrate binding alters the steric and non-covalent contacts near the gas binding site to stimulate O 2 activation. Understanding factors governing O 2 binding are key to understanding why the ferryl forms preferentially after the primary substrate is in position for subsequent hydroxylation.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 A key feature of FIH function is that O 2 activation is stimulated by the binding of the CTAD domain of the HIF transcription factor, 12 which ensures that the rate of CTAD hydroxylation is directly proportional to the concentration of O 2 (Scheme 1). 1315 Recently, it was shown that CTAD binding leads to a mixture of 6-coordinate (6C) and 5-coordinate (5C) Fe 2+ in FIH/CTAD, 7 suggesting that greater O 2 access to the Fe 2+ may only partially explain the increased O 2 reactivity upon CTAD binding. The rate-limiting step for O 2 activation by FIH occurs before early in turnover, making FIH an excellent enzyme to interrogate the link between O 2 activation and substrate hydroxylation in the broad class of αKG oxygenases.…”
Section: Introductionmentioning
confidence: 99%